The Checklist for Standard Methodological Requirements and Reporting of Economic Evaluation of Medicines in Slovakia - Bucek Psenkova, Maria; Hlavinkova, Lucia; Visnansky, Martin; Grega, Dominik; Ondrusova, Martina (Value in health regional issues, 2024)
OBJECTIVES: We have developed a scientifically well-grounded, methodological, and reporting checklist for economic evaluation (EE) of medicines in the Slovak health technology assessment process, which serves as a supplement to the Slovak pharmacoeconomic guidelines. METHODS: The checklist was developed using an iterative process in which items were generated and gradually added to the baseline checklist based on shortcomings identified in an analysis of Slovak EEs, using relevant published checklists, and Slovak, as well as international, methodological guidance that was identified in the systematic literature review. The selection of checklist recommendations, their clarity, and relevance to the Slovak setting were validated in the online survey. RESULTS: From the sample of 151 price and reimbursement submissions published between January 2018 and July 2021, almost half of them (n = 73) received at least 1 request from the Ministry of Healthcare to justify or modify the methodology used in the EE; and in 18 proceedings, a negative opinion was issued because of shortcomings identified in the EE. The 25-items preliminary checklist, resulting from an iterative working process, has been validated in an online survey conducted among members of ISPOR Chapter Slovakia. After incorporating relevant comments, the final proposal for the Slovak checklist consists of 55 recommendations. CONCLUSIONS: The research represented the first attempt to create a Slovak EE checklist, which serves as a part of ISPOR Slovakia pharmacoeconomic guidelines. Implementation of the checklist allows checking whether EE meets legislative and methodological requirements and thus helps in improving the appropriateness and standardization of EEs in Slovakia.
Keywords: Checklist; Economics, Pharmaceutical; Slovakia; lidé; Slovenská republika; guidelines; checklist; health economic evaluation; kontrolní seznam; ekonomika farmaceutická; Humans